Answer:
S - 32 + Aft (A = the length of the animals leg)
Step-by-step explanation:
Answer:
Plot the points in black and connect them.
Plot the point in blue and count up 3 and to the right 1. Plot and connect the points.
Step-by-step explanation:
Using your cursor/mouse, you will first choose the color black. Then you will plot the points given to you (2,2) and (5,8) by first finding the x-coordinate of (x,y). Start at 2 on the x-axis. Follow the grid line up two units so you will also be at the 2 on the y-axis. Plot or draw a dot/circle on this grid line. Go back to the x-axis and start again at 5 on the x-axis. Follow the grid line up eight units so you will also be at the 8 on the y-axis. Plot or draw a dot/circle on this grid line. Connect the dots for your line.
Using your cursor/mouse, you will choose the color blue. Then you will plot the point given to you (10,5) by first finding the x-coordinate of (x,y). Start at 10 on the x-axis. Follow the grid line up five units so you will also be at the 5 on the y-axis. Plot or draw a dot/circle on this grid line. Instead of plotting another point. This time you will count from the blue point up three units and over to the right one. Mark this grid line as a point. Now connect them.
Answer:treeeeeeeeeeeeeeeeeeeeeeee
reuwq9iasuoajkaseeeeeeeeeeeeeeeeeeeeeeeee
Step-by-step explanation:eeeeeeeeeeeeeeeeeeeeeeeeee
sjaiosjdisojkdisseeeeeeeeeeeeeeeeeeee
The picture is upside down my dude, delete the question, re-upload it and ill help you out.
Answer:
The roots of equations are as m =
And n =
Step-by-step explanation:
The given quadratic equation is 2 x² + 6 x - 1 = 0
This equation is in form of a x² + b x + c = 0
Let the roots of the equation are ( m , n )
Now , sum of roots = ![\frac{ - b}{a}](https://tex.z-dn.net/?f=%5Cfrac%7B%20-%20b%7D%7Ba%7D)
And products of roots = ![\frac{c}{a}](https://tex.z-dn.net/?f=%5Cfrac%7Bc%7D%7Ba%7D)
So, m + n =
= - 3
And m × n = ![\frac{ - 1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%20-%201%7D%7B2%7D)
Or, (m - n)² = (m + n)² - 4mn
Or, (m - n)² = (-3)² - 4 (
)
Or, (m - n)² = 9 + 2 = 11
I.e m - n = ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Again m + n = - 3 And m - n = ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Solving this two equation
(m + n) + ( m - n) = - 3 + ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
I.e 2 m = - 3 + ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Or, m = ![\frac{-3}{2} + \frac{\sqrt{11} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B2%7D%20%2B%20%5Cfrac%7B%5Csqrt%7B11%7D%20%7D%7B2%7D)
Similarly n =
Hence the roots of equations are as m =
And n =
Answer